2013
DOI: 10.3109/10641963.2013.804547
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte and platelet to lymphocyte ratio in patients with dipper versus non-dipper hypertension

Abstract: We demonstrated that patients with non-dipper hypertension had significantly higher NLR and PLR compared to dipper hypertension, which has not been reported previously. Moreover PLR more than 107 but not NLR was independent predictor of non-dipper status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
166
1
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(179 citation statements)
references
References 26 publications
4
166
1
8
Order By: Relevance
“…They release several types of cytokines and trigger the immune system and infl ammatory reactions. Previous studies have demonstrated that higher levels of NLR are associated with impaired cardiovascular outcomes (10)(11)(12)(13). NLR is not only associated with CVD, but also associated with chronic renal disease and several malignancies (11,13,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They release several types of cytokines and trigger the immune system and infl ammatory reactions. Previous studies have demonstrated that higher levels of NLR are associated with impaired cardiovascular outcomes (10)(11)(12)(13). NLR is not only associated with CVD, but also associated with chronic renal disease and several malignancies (11,13,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio (NLR) which can be derived from the white blood cell count is an inexpensive, routinely used, reproducible test. NLR has been proposed as a novel biomarker for systemic infl ammatory response in several diseases (10)(11)(12)(13). Previous studies have shown that NLR is associated with poor clinical outcomes in CVD and it is also a predictor for CVD (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…PLR has been recently suggested to be a marker of thrombotic and inflammatory condition. In the literature, it was shown that valvular heart diseases, acute coronary syndromes, hypertension, end-stage renal diseases, and other diseases may potentially affect the PLR [2][3][4][5][6]. In the study of Xing Li et al [1], patients with previous and/or secondary cancers were excluded, while such as heart diseases which is very common in old people (age 57 (19-86)) were not mentioned.…”
mentioning
confidence: 99%
“…13 It causes not only cardiovascular disease, but also numerous chronic diseases such as cancers, diabetes mellitus, hypertension, connective tissue disease, and chronic kidney disease. [14][15][16][17][18] Figure 1: Receiver operating characteristic analysis for neutrophil-to-lymphocyte ratio to predict abnormal coronary angiography (area under curve is 0.726).…”
Section: Discussionmentioning
confidence: 99%